Implementation of Transformational Leadership by School Principals in Improving Services for Students with Special Needs - Wahyu Candra Dewi; Yovitha Yuliejantiningsih; Soedjono Soedjono (Journal of Innovation and Research in Primary Education, 2026)
Inclusive education implementation in resource-constrained primary schools requires effective leadership to overcome structural limitations. This study examines how transformational leadership by school principals improves educational services for students with special needs in contexts lacking specialized support personnel. Employing a qualitative case study design, this research investigated transformational leadership implementation at SDN Bergas Lor 02, Semarang Regency, Indonesia. Data were collected through semi-structured interviews with the principal and six classroom teachers, three-month participant observations, and document analysis. Thematic analysis identified patterns across the four transformational leadership dimensions: idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. The principal systematically enacted transformational leadership through moral exemplarity establishing inclusive culture, inspirational messaging maintaining collective optimism despite resource constraints, facilitation of collaborative professional learning through structured sharing sessions, and differentiated support calibrated to individual teacher and student needs. Unexpected findings revealed the principal's strategic creation of peer mentoring networks and effective reframing of setbacks as learning opportunities. Findings demonstrate that transformational leadership dimensions operate synergistically to maximize human capital when material resources remain limited. The study contributes the concept of "productive recontextualization"—adapting leadership principles to resource-constrained contexts through low-cost mechanisms while maintaining theoretical fidelity. Results suggest leadership development represents a high-leverage strategy for advancing inclusive education in under-resourced settings.